KOMPARASI PILIHAN PENGGUNA MODA ANGKUTAN LAUT DI PELABUHAN MUARA ANGKE ANTARA KAPAL DISHUB DAN KAPAL TRADISIONAL - Adi Nursalim; Tri Mulyono (Universitas Negeri Jakarta, 2019)
The sea transportation mode is a means or tool used by people to move from one place to another. Sea freight mode in DKI Jakara is expected to provide quality service to the users of the transportation services as well as the service users on board, other than that the passenger characteristics strongly affect passengers in choosing Mode of transportation. Based on the user data of traditional vessels majority of the female users differ from the Dishub ship of the majority of male users. The user's age for both ships is the majority of the age range of 21-30 years, including the majority work of students. The level of user earning both traditional and dishub vessels does not differ the majority have not been income according to the type of work. The purpose and frequency of user journeys of traditional vessels and dishub vessels are no different, with the purpose of the majority being a one-time recreation a year. The study aims to determine which variables will result in factors affecting the perpetrators and the probability of selecting the mode located in the Muara Angke port between the Dishub ship and the traditional vessel. Data processing uses the Serqual method to determine the number of samples from the population and SPSS program to find out the factors affecting the selection of the modes of traditional vessels of Dishub and vessels.